2021
DOI: 10.3390/ijerph182211739
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Mindfulness-Based Intervention for Chronic Migraine and High Frequency Episodic Migraine in Adolescents: A Pilot Single-Arm Open-Label Study

Abstract: In this single-arm pilot open-label study we examined the effect of a mindfulness-based intervention on reduction of headache frequency after 12 months in adolescents aged 12–18 with chronic or high-frequency migraine without aura. Adolescents were recruited at the headache center of the C. Besta Neurological Institute and followed-up for 12 months. The mindfulness-based intervention was delivered in small groups and consisted of six weekly group sessions of guided meditation, and one booster session 15 days a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 46 publications
1
7
0
Order By: Relevance
“… 58 The evidence for ACT in the treatment of pediatric chronic pain is growing. 59 Two investigations of mindfulness-based interventions for chronic migraine in children and adolescents, including one recent open-label trial, have shown promising results in reducing migraine-related disability, 60 , 61 mirroring findings from trials of mindfulness-based interventions among adults with migraine. 62 , 63 …”
Section: Preventive Treatmentsmentioning
confidence: 91%
See 1 more Smart Citation
“… 58 The evidence for ACT in the treatment of pediatric chronic pain is growing. 59 Two investigations of mindfulness-based interventions for chronic migraine in children and adolescents, including one recent open-label trial, have shown promising results in reducing migraine-related disability, 60 , 61 mirroring findings from trials of mindfulness-based interventions among adults with migraine. 62 , 63 …”
Section: Preventive Treatmentsmentioning
confidence: 91%
“…58 The evidence for ACT in the treatment of pediatric chronic pain is growing. 59 Two investigations of mindfulness-based interventions for chronic migraine in children and adolescents, including one recent open-label trial, have shown promising results in reducing migraine-related disability, 60,61 mirroring findings from trials of mindfulnessbased interventions among adults with migraine. 62,63 Other Preventive Treatment Options Clinical research efforts have been devoted to studying alternative treatments that reduce risks associated with traditional pill-based migraine therapies given current practice guidelines.…”
Section: Dovepressmentioning
confidence: 92%
“…The intervention group received mindfulness training and the control group received health education unrelated to the content of the intervention material. Since the mindfulness course requires the students of intervention group to participate in and receive training, this study is an open-label trial, which does not involve blind methods ( 35 ). MLWC, the online intervention course used in this study, was developed by two Chinese psychiatrists, one of whom has been certified in the Training of Mindfulness Facilitation program at the Mindful Awareness Research Center of University of California, Los Angeles (UCLA).…”
Section: Methodsmentioning
confidence: 99%
“…Some pilot studies demonstrated the acceptability and feasibility of a mindfulness-based treatment for adolescents with recurrent headaches ( 59 , 60 ).…”
Section: Therapymentioning
confidence: 99%
“…Evidence for the efficacy of psychological interventions for the treatment of headaches in youth has grown substantially over the past several decades (55,56,(58)(59)(60). There is a strong and growing body of evidence demonstrating the effectiveness of psychological approaches, primarily cognitivebehavioral therapy (CBT), for treating migraine in children and adolescents (37,38,54,55).…”
Section: Therapymentioning
confidence: 99%